2003
DOI: 10.18553/jmcp.2003.9.5.401
|View full text |Cite
|
Sign up to set email alerts
|

Weight Uniformity of Split Tablets Required by a Veterans Affairs Policy

Abstract: OBJECTIVE: To split several tablet products relevant to the Veterans Affairs (VA) Maryland Healthcare System and assess whether the resulting half tablets provide equal doses.METHODS: From a VA list of products that are required to be split, 7 products were evaluated, along with 5 other commonly split tablet products. A trained pharmacy student split tablets using a tablet splitter provided by the VA. Half tablets were assessed for weight uniformity.RESULTS: Of the 12 products subjected to splitting, 8 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 19 publications
0
38
0
1
Order By: Relevance
“…A similar study performed by Polli et al assessed content uniformity through the analysis of half-tablet weights using the same adapted USP methods as used by Teng et al 7 In contrast to the results found by Teng et al, this study, performed at a Department of Veterans Affairs (VA) center, found that 8 out of 12 medications split with a tablet-splitting device passed the adapted uniformity test. 7 Another study analyzed the drug weight uniformity of cyclobenzaprine tablets split in half using either a tablet splitter or a kitchen knife.…”
Section: What This Study Addsmentioning
confidence: 71%
See 1 more Smart Citation
“…A similar study performed by Polli et al assessed content uniformity through the analysis of half-tablet weights using the same adapted USP methods as used by Teng et al 7 In contrast to the results found by Teng et al, this study, performed at a Department of Veterans Affairs (VA) center, found that 8 out of 12 medications split with a tablet-splitting device passed the adapted uniformity test. 7 Another study analyzed the drug weight uniformity of cyclobenzaprine tablets split in half using either a tablet splitter or a kitchen knife.…”
Section: What This Study Addsmentioning
confidence: 71%
“…7 Another study analyzed the drug weight uniformity of cyclobenzaprine tablets split in half using either a tablet splitter or a kitchen knife. 8 The results showed that both methods resulted in a wide variation in fragment weight between 49.9% to 149.5% of the theoretical weight (defined as one-half of the mean weight of the intact tablet) using a kitchen knife and 69.4% to 130.2% using the tablet splitter.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Another study performed by Polli et al (2003) found that 4 of 12 medications failed the weight uniformity test with a variation up to 20% of the theoretical half weight, according to an adapted USP Uniformity of Dosage Units criterion for whole tablets. They also pointed that split-tablets of lovastatin, lisinopril, rofecoxib, and simvastatin were out of %RSD specification, with %RSD values ranging from 10.4 to 21.1% (30).…”
Section: Resultsmentioning
confidence: 99%
“…10 One source identified annual savings of approximately $342,000 through tablet-splitting in a plan with $10 million in annual pharmacy benefit expenditures. 11 In 2004, the VA announced that splitting simvastatin tablets saved $46.5 million systemwide in fiscal year 2003.…”
Section: Tablet Splitting As a Managed Care Issuementioning
confidence: 99%